2019
DOI: 10.3390/coatings9100645
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of RF Sputtering Conditions on the Physical Characteristics of Deposited GeGaN Thin Film

Abstract: Ge0.07GaN films were successfully made on Si (100), SiO2/Si (100) substrates by a radio frequency reactive sputtering technique at various deposition conditions listed as a range of 100–400 °C and 90–150 W with a single ceramic target containing 7 at % dopant Ge. The results showed that different RF sputtering power and heating temperature conditions affected the structural, electrical and optical properties of the sputtered Ge0.07GaN films. The as-deposited Ge0.07GaN films had an structural polycrystalline. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…It was found that the root mean square (RMS) roughness of PET, P4 (2.6 μm), and P4 (126 μm) decreased after coating with PMMA, dropping from 1.1 nm, 8.6 nm, and 0.6 nm to 0.3 nm, 0.4 nm, and 0.3 nm, respectively. Moreover, all values were lower than the 1.3 nm roughness of commercially available glass substrates [ 28 ]. It is noteworthy that, as observed in Figure 6 c,e, pore formation occurred in the pure P4 films of both thicknesses.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the root mean square (RMS) roughness of PET, P4 (2.6 μm), and P4 (126 μm) decreased after coating with PMMA, dropping from 1.1 nm, 8.6 nm, and 0.6 nm to 0.3 nm, 0.4 nm, and 0.3 nm, respectively. Moreover, all values were lower than the 1.3 nm roughness of commercially available glass substrates [ 28 ]. It is noteworthy that, as observed in Figure 6 c,e, pore formation occurred in the pure P4 films of both thicknesses.…”
Section: Resultsmentioning
confidence: 99%
“…Thao et al [23] investigate Ge 0.07 GaN films prepared by radio frequency reactive sputtering changing RF sputtering power and heating temperature conditions. Structure, optical and electrical characteristics of the films are significantly affected by both deposition parameters and with the best electronic transport properties and the lowest photoenergy produced for the deposited-150 W Ge 0.07 GaN film.…”
Section: This Special Issuementioning
confidence: 99%
“…The results determined that these deposited Sb-x-GaN films converted to a p-semiconductor at x = 0.07, 0.14, and 0.2. The p-SbGaN/n-Si(100) heterojunction diodes performed successfully and their electrical characteristics at room temperature were thoroughly investigated [18] In 2019, our previous work was performed in conditions that affected the electrical, optical, and structural properties of the GeGaN thin films grown using RF reactive sputtering [19]. At the highest temperature of 400 • C, the Ge 0.07 GaN film acted as an n-semiconductor, had a smaller bandgap energy of 3.02 eV, and achieved a higher carrier concentration of 1.30 × 10 18 cm −3 , an electrical conductivity of 1.46 Scm −1 , and an electron mobility of 7 cm 2 V −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%